Student Perceptions of Faculty Mindset - Christy Jarrard; Deborah Richardson; Robert Bledsoe (Journal of the Scholarship of Teaching and Learning)
This study investigates the influence of instructor mindset on student perceptions. Due to the need for increasing science, technology, engineering, and mathematics (STEM) student retention and the issue of underrepresentation of minority groups in STEM disciplines, we also examined whether instructor mindset impacts underrepresented students more than represented students in the context of STEM education. Undergraduate student participants (N = 273) reviewed growth and fixed mindset syllabi and responded to a questionnaire to assess perceptions about their likely response and the professor. The significant main effect of faculty mindset revealed that students anticipated better grades and reported a more positive view of the instructor, greater self-efficacy, and higher expectations the professor would treat them fairly after reading the growth mindset syllabus than after reading the fixed mindset syllabus. Females reported lower expected grades, less self-efficacy, and lower expectations of fair treatment than males after reading the fixed syllabus; there were no gender differences after reading the growth mindset syllabus. The results of underrepresented racial/ethnicity group analyses were less clear cut. Our findings, alongside similar research, suggest that students have more positive perceptions of their ability to succeed when an instructor endorses a growth mindset than when an instructor endorses a fixed mindset. Implications include interventions to enhance growth-mindset orientation among instructors.